Conversations from the Margins: Disability and the Path to Inclusion - Mansilla, Juan Camilo (Critical Disability Discourses, 2025)
This perspectives piece offers an exploration of the daily lives of people with disabilities living in Quebec, through a series of personal accounts. More than just an academic analysis, it serves as an invitation to reflect on the role of disability in our society, the fragility of existence, and the strength that emerges from it. By highlighting the voices of those often reduced to study subjects (Guenther, 2009), this perspectives piece reclaims their humanity and advocates for the (re)introduction of real voices and bodies in social research (Edwards, 2020), essential to our human essence, as narrative shapes and gives meaning to human actions (Sarbin, 1986). The testimonies of Camelia, Wilbur, and Henry (pseudonyms) illustrate the complexity of living through migration and social isolation, employment discrimination, and the struggle against overwhelming medical diagnoses. Their stories reveal both the harshness of their reality and the beauty of everyday life, where resilience and hope are woven into the fabric of their days. Through their journeys, the piece reminds us that inclusion goes beyond physical accessibility, engaging social bonds, and mutual recognition. Keywords: Disability, Daily Life, Inclusion, Resilience, Testimonials